Impact of the Covid-19 Pandemic on Vaccination Coverage in Brazilian States: Impact of COVID-19 on Vaccination Brazil - Colla, Francieli da Costa (2023)
Objective: Assess the impact of the COVID-19 pandemic on general vaccination coverage indicators in Brazilian states. Methods: A descriptive ecological time series study with Brazilian federative states and general vaccination coverage between 2013 and 2021 was carried out as the unit of analysis. Data were collected in the National Immunization Program Information System via DATASUS, processed, and analyzed in Microsoft Office Excel software. The descriptive statistical analysis comprised the calculations of measures of central tendency and dispersion, in addition to the difference and percentage variation, considering the changes in the historical series, with a comparison between the period before the pandemic (2018-2019) and the pandemic period (2020-2021). Results:All Brazilian states reduced overall vaccination coverage during the COVID-19 pandemic compared to previous years. The variation in the decline in vaccination coverage presented inequalities between states, understood as health inequities. Considering the general average and the declining percentage during the pandemic, the states in the best relative situation are Santa Catarina, Tocantins, Distrito Federal, Minas Gerais, Paraná, and Mato Grosso. The worst situations are Amapá, Rio de Janeiro, and Acre. Conclusion: The pandemic impacted on the vaccination coverage coefficients in Brazilian states resulting in regional inequalities. The study contributes to understanding the immunization scenario in the country despite the limitations intrinsic to the ecological nature of the approach. The revitalization of the National Immunization Program requires joint efforts from society, including health education actions and improvement of financing and management processes.